The evolving role of MRI in pulmonary sarcoidosis: Comparative analysis with PFTs and progression markers - Griffin, Ian; Pasini, Romulo; Mehrad, Borna; Al-Ani, Mohammad; Mohammed, Tan-Lucien; Gomez Manjarres, Diana; Patel, Divya; Altmayer, Stephan; Marchiori, Edson; Hochhegger, Bruno (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Sarcoidosis is a systemic illness with unclear etiology that commonly affects the lungs and intrathoracic lymph nodes. Chest radiography, CT, and, more recently, MRI can be used for assessment, with bilateral hilar lymph node enlargement and interstitial lung disease being common observations.Objectives: In adults diagnosed with pulmonary sarcoidosis, how do chest radiography, CT, and MRI compare in the assessment of disease progression?Study Design and Methods: This is a prospective study of 77 adults diagnosed with pulmonary sarcoidosis. Each patient underwent pulmonary function testing, chest radiography, HRCT and MRI within a span of 90 days. Chest radiographs were scored using the Scadding stage classification system. HRCT and MRI were both scored using the Scleroderma Lung Study I system. Pulmonary function was re-assessed after 12 months, with progression of disease defined as worsening symptoms AND ≥5% reduction of forced vital capacity (FVC). Disease progression was used as the gold standard to calculate area under the curve (AUC) of the receiver operating characteristic plot for radiography, HRCT, and MRI.Results: There is strong correlation between chest radiography and MRI (r=0.649, P < 0.001), and CT and MRI scores (r=0.851, P < 0.05). CT and MRI scores correlated with forced vital capacity (MRI: r =-0.584, P < 0.001; CT: r =-0.308, P = 0.049) and diffusing capacity of the lung for carbon monoxide (MRI: r =-0.564, P =0.004; CT r =-0.216, P = 0.017). AUCs for chest radiography, MRI and CT scores were 0.70 (0.49-0.85), 0.71 (0.42–0.85), and 0.68 (0.26–0.90), respectively. Multivariate regression analysis of CT and MRI scores demonstrated statistically significant prediction of progressive disease by both modalities.Conclusion: MRI may be a viable alternative to HRCT in the assessment of lung parenchyma and disease progression in patients with pulmonary sarcoidosis.